THE IMPACT OF WRITTEN CORRECTIVE FEEDBACK TOWARDS THE SENIOR HIGH SCHOOL STUDENTS’ WORK: TEACHER’S AND STUDENTS’ PERCEPTIONS - Indra Yoga Prawiro (Universitas Majalengka, 2020)
This study figures out the teacher and students’ perceptions toward teacher’s written corrective feedback and to describe how the teacher gives written corrective feedback on the students writing. The writer uses descriptive case study as the design of the research with three techniques of data collection. Questionnaire and interview are used to know teacher’s and students’ perception toward written feedback. Students’ document used to analyse teacher’s way in providing written corrective feedback on student’s task. The result of the research showed that the teachers used almost categories of written corrective feedback. As the findings of the research showed that teachers mostly use direct corrective feedback in providing written feedback on students’ work. Also the students mostly like when the teacher providing direct corrective feedback and the language that used by teachers in giving explanation on students mistakes. Whereas students has understanding in what is feedback actually and how importance feedback in the teaching and learning process. Also they have positive acceptance toward teacher’s written corrective feedback because they are aware to improve their skill. From 19 students, the average of students’ answer in percentage related to teacher’s way in giving written corrective feedback is 44 % who chose “Always”, 34 % who checklist “Sometimes”, and 22 % who answer “Never”. Moreover, for preferences would students’ like when receiving written corrective feedback, the result showed that 67 % of students chose first option “Like”, 23 % checklist “Neutral”, and 10 % answered “Dislike”. It is indicated various perception from students.